A novel stereotactic prostate biopsy system integrating pre-interventional magnetic resonance imaging and live ultrasound fusion - Hadaschik, Boris; Kuru, Timur Hasan; Tulea, Corina; Rieker, Philip; Popeneciu, Valentin; Simpfendörfer, Tobias; Huber, Johannes; Zogal, Pawel; Teber, Dogu; Pahernik, Sascha; Röthke, Matthias C.; Zamecnik, Patrik; et al. (The journal of urology, 2011)
Purpose: We developed an effective way to precisely diagnose prostate cancer using a novel prostate biopsy system that integrates pre-interventional magnetic resonance imaging with peri-interventional ultrasound for perineal navigated prostate biopsy. Materials and Methods: A total of 106 men with findings suspicious for prostate cancer (median age 66 years, prostate specific antigen 8.0 ng/ml and prostate volume 47 ml) underwent multiparametric 3 Tesla magnetic resonance imaging. Suspicious lesions were marked and data were transferred to the novel biopsy system. Using a custom-made biplane transrectal ultrasound probe mounted on a stepper we gathered 3-dimensional ultrasound data and fused them with magnetic resonance imaging data. As a result, suspicious magnetic resonance imaging lesions were superimposed over the transrectal ultrasound data. Three-dimensional biopsy planning was done, including systematic biopsies. Perineal biopsies were taken under live ultrasound guidance and the precise site of each biopsy was documented in 3 dimensions. We evaluated feasibility, safety and cancer detection. Results: Prostate cancer was detected in 63 of 106 patients (59.4%). Magnetic resonance imaging findings correlated positively with histopathology in 71 of 103 patients (68.9%). In magnetic resonance imaging lesions marked as highly suspicious, the detection rate was 95.8% (23 of 24 cases). Lesion targeted cores had a significantly higher positivity rate than nontargeted cores. The procedural targeting error of the first 2,461 biopsy cores was 1.7 mm. Regarding adverse effects, 2 patients experienced urinary retention and 1 had a perineal hematoma. Urinary tract infections did not develop. Conclusions: Perineal stereotactic prostate biopsies guided by the combination of magnetic resonance imaging and ultrasound enable effective examination of suspicious magnetic resonance imaging lesions. Each biopsy core taken is documented accurately for its location in 3 dimensions, enabling magnetic resonance imaging validation and tailored treatment planning. The morbidity of the procedure was minimal.
Submitted for publication April 20, 2011
Gesehen am 15.07.2021